Influence of the role defended during a role-playing on pre-service elementary science teachers' scientific knowledge - Cruz-Lorite, Isabel María; Cebrián-Robles, Daniel; Acebal, María del Carmen; Blanco-López, Ángel (My University, 2021)
This work shows a study about the influence of the role defended during the participation in a role-playing game about nuclear energy on the pre-service elementary science teachers’ scientific knowledge. 74 pre-service teachers participated in four role-playing games and a mixed approach was followed for data analysis, through a pre-test/post-test. The results suggest that the pre-service teachers who had to defend a role with a position against their personal point of view could achieve greater scientific knowledge learning. Furthermore, some limitations of this study are discuss.
Keywords: Educación; Initial Teacher Education (pre-service); Simulations; Socioscientific Issues; Role-playing game; Nuclear energy